APPLICATION OF ISLAMIC VALUES OF SHARIA COOPERATIVES IN INDONESIA - Ma'ruf, Aminudin; Wijayanto, Agung Dwi; Aulia, Sausan Liski (Maqdis: Jurnal Kajian Ekonomi Islam, 2023)
This study discusses the application of Islamic values in sharia cooperatives in Indonesia. Islamic values in sharia cooperatives properly and correctly reflect the welfare and trust of sharia cooperative customers. This study also aims to determine the Islamic values applied to sharia cooperatives in Indonesia and to find out how the implementation of Islamic values is carried out in their business activities. This paper adopts field research with qualitative research methods. Data collection techniques in this study by means of observation, interviews, online databases, and documentation. The results of the study indicate that Islamic values applied to sharia cooperatives in Indonesia include honesty values, consistency values, communicative values, trust values, equality values, monotheism values, ta'awun values, and family values. The application of Islamic values carried out by sharia cooperatives in Indonesia by stipulating that customers in entering into agreements must be honest, in carrying out all transactions correctly and correctly according to sharia rules, offering sharia cooperative products to the public, and expecting customers to provide full responsibility to the sharia cooperative. Consequently, sharia cooperatives in Indonesia must improve even more regarding the applied Islamic values, and are expected to maintain and carry out properly and correctly the implementation of Islamic values.